(3GdfXGe GdGfVHGWj ddbVGI hGdeOYjf GdYGejf aj GdJTQjY GdebGQf (B/s - (3GdYHhOj, YKeGf SdeGf ZjdGfs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2015)
(3jSdW gPG GdcJGH GdVhA Ydi adSaI GdfXGe GdbGfhfj GdPj jMce eSGAdI GdYGedjf aj GdSdWI GdbVGFjI ef GdbVGI hGdeOYjf GdYGejf hcjajI bjGe GdeSDhdjI GdbGfhfjI ddaFI GdePchQI hELQGAGJ GdeSGAdI hCUhdgG hGdBKGQ GdeJQJHI YdjgG Vef efgL JMdjdj hebGQf ceG jHMK GdfXGe GdEfVHGWj ddbVGI hGdeOYjf GdYGejf eeG jaUM Yf GdETGQI aj GdhbJ PGJg Edi GdQcGFR GdCSGSjI GdJj jLH eQGYGJgG aj eSGAdJge HeG JMaX eGA hLg GdbVGA hjUhf GSJbdGdg(B.s
(3HHdjhLQGajI (B: (3UaMI (B239-244.s
Keywords: (3GdbVGIs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3GdYQGbs; (3GdbVGIs -- (3hVY bGfhfj, bhGfjf, EdN(B.s -- (3GdHdGO GdYQHjIs; (3GdbVGAs -- (3bhGfjf hJTQjYGJs -- (3JhLjg egfjs; (3GdGNJUGU GdbVGFjs -- (3GdYQGbs